A Systematic Review of Enhancing English Learning Motivation through Mobile Learning and Gamified Activities - Ahmad Zidan Al Gifari; Cintria; Mira Fadellah Oktasya; Nabila; Okta Festyanisa (Yayasan Al Hidayah, 2025)
This study aims to systematically review the role of mobile learning and gamification in enhancing English learning motivation within the ASEAN context. Using the PRISMA 2020 framework, fourteen journal articles published in 2025 were analyzed. The findings reveal that gamification elements such as points, badges, leaderboards, and interactive platforms like Quizizz, Blooket, Kuartet, and gamified MOOCs consistently foster learners’ engagement, confidence, and participation. Mobile learning was also found to support autonomy and flexibility, while its effectiveness strongly depends on students’ ICT competence and perceived usefulness. Despite these positive outcomes, challenges remain, including limited digital literacy, teacher readiness, and infrastructure barriers, particularly in under-resourced areas. Moreover, although motivation increased significantly, measurable academic performance improvements were less consistent, emphasizing the need for robust pedagogical integration. Overall, this review highlights that mobile learning and gamification are promising strategies to address motivational issues in English learning, but their long-term success requires teacher training, adequate infrastructure, and culturally responsive instructional design.